Scattering for newtonian evolution - Cortés, Victor H.; Fernández, Claudio (Ciência e Natura, 1996)
In the study of many phenomena in the physical world, one is interested in describing the long time behavior of certain observables. That is the case, for example, of the principles that govern the radar, the sonar and the disperson of ligtht waves.